2001
DOI: 10.1892/0891-6640(2001)015<0355:rbprft>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Bactericidal/Permeability-Increasing Protein (rBPI21) for Treatment of Parvovirus Enteritis: A Randomized, Double-Blinded, Placebo-Controlled Trial

Abstract: We evaluated the ability of an antimicrobial and endotoxin-neutralizing agent, the recombinant amino terminal fragment of bactericidal permeability-increasing protein (rBPI21), to decrease plasma endotoxin concentration and severity of clinical signs of canine parvovirus and to improve survival. This randomized, double-blinded, placebo-controlled clinical trial included 40 client-owned dogs and 9 normal puppies from a closed research colony. Dogs weighing >5 kg (11 lb) with fecal antigen-confirmed parvovirus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
22
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 10 publications
2
22
1
2
Order By: Relevance
“…D isease caused by canine parvovirus (CPV) affects more than a million dogs per year in the United States. 1 Parvoviral infection is characterized by severe enteritis, anorexia, vomiting, hemorrhagic diarrhea, and shock. 2 The published fatality rate is 16-35%, 3 although intensive therapy has achieved survival rates of up to 85-96%.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…D isease caused by canine parvovirus (CPV) affects more than a million dogs per year in the United States. 1 Parvoviral infection is characterized by severe enteritis, anorexia, vomiting, hemorrhagic diarrhea, and shock. 2 The published fatality rate is 16-35%, 3 although intensive therapy has achieved survival rates of up to 85-96%.…”
mentioning
confidence: 99%
“…2 The published fatality rate is 16-35%, 3 although intensive therapy has achieved survival rates of up to 85-96%. 1,2 Treatment is primarily supportive and symptomatic. Novel adjunctive drugs have been investigated, but results have been disappointing or variable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Release of free lipopolysaccharide is a potent stimulator of sepsis, so rBPI21 binding prevents lipopolysaccharides from interacting with host cells, reducing the septic response. Although shown to be beneficial when used in humans with meningococcal sepsis (Levin et al, 2000), the only veterinary study on rBPI21 use on dogs with CPV enteritis reported no benefit (Otto et al, 2001).…”
Section: Additionalpotentialtreatmentoptionsmentioning
confidence: 99%
“…Since the virus was first discovered in 1978 it has evolved and there are now three known strains that can cause enteritis; CPV-2a, b and c. In experimentally infected dogs, mortality without treatment is as high as 91% (Prittie, 2004). Although no definitive treatment has been reported, survival rates with intensive therapy can be up to 90%; however, survival rates in tertiary, referral hospitals have been shown to be higher than those in first opinion practice (Otto et al, 2001). This article will cover the pathophysiology of CPV infection and discuss the current and experimental treatments available.…”
mentioning
confidence: 99%